(untitled) (Global Conference on Medical and Health Sciences, 2026)
The article examines the inclination of the rural population to treat cardiovascular and respiratory diseases using the example of the Samarkand region. This indicator was assessed using the widely used Morisky-Green questionnaire in the world. It is indicated that patients have a low propensity for treatment, one of the reasons for which is non-compliance with indications, as well as insufficient communication between the doctor and the patient. Successful management of chronic diseases requires not only effective medical procedures but also the active participation of patients in the treatment process. The main factor determining the effectiveness of treatment for non-communicable chronic diseases is predisposition to treatment. Therefore, it is advisable to accelerate the integration of modern technologies into practical medicine.